Analisis Lingkungan Industri pada Pelaku Usaha Mikro di Hamzah Batik Yogyakarta - Sir Kalifatullah Ermaya (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2023)
This research was conducted on 30 creative SMEs in Yogyakarta who supply their products to Hamzah Batik. The classification of the craftsmen are: snacks, traditional home decorations, aromatherapy oils, wood crafts, silver crafts, batik bags, batik shoes and sandals, batik fabrics, traditional herbs and herbs as well as luxury materials such as jars and paintings. The results show that by using descriptive statistical analysis of the industrial analysis model created by Porter, the